Psychosocial issues of hearing impaired school children: a psychometric approach - Qurat-Ul-Ain; Sadia Saleem; Anila Sarwar; Zahid Mahmood (Journal of the Pakistan Medical Association, 2020)
Objective: To develop a valid and reliable scale for measuring psychosocial issues of hearing-impaired school children. Method: The cross-sectional study with four stage model of scale development was conducted at Multan, Muzafargarh, and Dera Ghazi Khan Pakistan from August 2018 to January 2019. The four stages were item generation, expert validation, conversion of scale into sign language and psychometric study. The sample comprised hearing-impaired school children aged 18-23 years who were studying Special Education schools in Multan, Pakistan. Results: Of the 230 subjects, there were 110(47.8%) boys and 120(52.2%) girls. The overall mean age was 19.90+/-2.46 years.Exploratory factor analysis with varimax rotation revealed 26 items in ‘Depressive Affect’, ‘Social Isolation’ and ‘Feeling of Anger’ sub-scales with high internal consistency (r=0.85) and validity (r=-0.32). Conclusion: The internalised nature of psychosocial issues of children with hearing impairment needs timely identification and intervention so that silent suffering can be prevented to improve psychosocial functioning of such children. Key Words: Hearing impairment, Psychosocial issues, Gender, Age, Reliability, Validity. Continuous...